Western and Islamic Constitutionalism - Gustavo Gozzi (Athena, 2025)
This essay aims to develop the comparison between Western constitutionalism and Islamic constitutionalism. In the Western tradition the term constitutionalism points to the limitation of government through law. There have been different models of constitutionalism, in particular the American and the French ones, that can be understood in the light of the two interpretive categories of constitutional democracy and legislative democracy, respectively. The developments of contemporary constitutionalism appear very complex, as today's constitutions are the reflection of the cultural, religious, social and political pluralism of current societies. Therefore, the centrality of interpretation is imposed, whose complexity derives from the fact that pluralistic constitutions merge legal issues and moral issues together. About Islamic constitutionalism some Islamic thinkers consider secularism a philosophy, while Islam is another form of philosophy, which has its own vision of human life, rights and duties. In this perspective it follows that it is reasonable to think that constitutionalism can be achieved differently in different societies depending on the conceptions of rights and duties that are accepted and shared.